Financing climate change mitigation: An assessment of the private sector investment opportunities in Ghana. Issue 1 (22nd July 2019) - Ahenkan, Albert
Abstract: The funding required for climate mitigation in Africa is estimated at 10 billion U.S. dollars annually. Unfortunately, the contributions by advanced countries will not be enough to meet the mitigation needs of developing countries. Emerging economies like Ghana have low financial capacity to effectively mitigate the harsh impacts of climate change. However, the proportion of private sector investment for climate change mitigation (CCM) keeps increasing—making it a major source of climate change finance. The paper examined the investment opportunities in CCM for private firms in Ghana. The study used qualitative research approach through in‐depth interviews with 25 private sector organisations, key development partners, and climate change experts and policy makers. The study found a number of opportunities for private sector investment in energy, agriculture, transport, waste, industry, and buildings in Ghana. The private sector has competencies, which can make a unique contribution to climate mitigation through investment in innovative technology and capacity building. The study revealed a number of barriers, which are hindering the private sector from investing in CCM in Ghana. The paper urged the government to create awareness of the investment opportunities and provide incentives to attract the private firms to scale up climate change financing and investment in Ghana.